2013
DOI: 10.1021/ie403310d
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Ethylene/1-Octene Copolymers by High-Temperature Thermal Gradient Interaction Chromatography

Abstract: High-temperature thermal gradient interaction chromatography (HT-TGIC) was recently introduced into the area of polyolefin analysis. This new technique uses commercially available Hybercarb columns to separate polyolefin chains based on their interaction with the porous graphitic carbon stationary phase in a temperature gradient mode. In this paper, a systematic study of HT-TGIC operation conditions is presented for ethylene/1-octene copolymers and their blends. One of the objectives of this investigation is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 20 publications
5
38
0
Order By: Relevance
“…In the figures below, the upper and lower temperatures used in the cooling cycle are indicated between square brackets, for instance, [155–90 °C]. The detailed description of the experimental work was explained in our previous publication . In this previous study, heating rate (HR) and sample size (SZ) were found to be the most important operational conditions affecting HT‐TGIC profiles of individual resins and their blends.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…In the figures below, the upper and lower temperatures used in the cooling cycle are indicated between square brackets, for instance, [155–90 °C]. The detailed description of the experimental work was explained in our previous publication . In this previous study, heating rate (HR) and sample size (SZ) were found to be the most important operational conditions affecting HT‐TGIC profiles of individual resins and their blends.…”
Section: Methodssupporting
confidence: 93%
“…The effects of the operating conditions on HT‐TGIC profiles were investigated in our recent study . The results of this study indicated that the chromatograms of individual resins and their blends were independent of the cooling rate.…”
Section: Introductionsupporting
confidence: 93%
“…For EP rubbers as well as for PP‐EPR reactor blends, TGIC remains insensitive for some compositions even if improved experimental protocols are applied. It will be interesting to see if a change in mobile phase broadens the accessible ethylene content range . This will be the subject of forthcoming investigations and will be of significant interest due to the fact that all industrially relevant EP rubbers have comonomer contents below 60 mol% ethylene.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, thermal gradient interaction chromatography (TGIC) has been introduced where a single solvent is used as mobile phase enabling the usage of various detectors such as infrared (IR), light scattering (LS), and online viscometer . This method has been used extensively for the chemical composition analysis of LLDPE . While SGIC operates at temperatures above melting, and thus, sample crystallinity does not influence the fractionation process, TGIC uses a temperature gradient starting at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation